The Innovative concept and Issues Concerning the Non-Custodial Sentence in Nigerian Criminal Justice System - Oaihimire, Idemudia Edetalehn; Aidonojie, Paul Atagamen (Law Development Journal, 2023)
It is apt to state that the challenges currently encountered in the Nigerian criminal justice system, is that the Nigerian correctional centers are densely populated with awaiting trial suspects and in a highly deplorable condition. In a renewed effort to attend to the Nigerian correctional centres' appalling state, the National Assembly enacted the Administration of Criminal Justice Act (ACJA) 2015 and the Nigerian Correctional Services Act (NCSA) 2019. These laws are meant to promote the efficient management of the criminal justice system and to address issues (such as a non-custodial sentence) that were not hitherto covered under the repealed Nigerian Prisons Act, in line with the internationally accepted standards. However, despite the innovation brought by these laws, there are some challenges affecting its smooth implementation. It is in this regard, that this study tends to embark on a hybrid method of study in ascertaining the relevance of non-custodial sentences in Nigeria's criminal justice system laws and its challenges. Questionnaires were sent to 327 of respondents, descriptive and analytical methods were used in analyzing the data generated. The study, therefore, found that the introduction of a non-custodian sentence has greatly enhanced the Nigerian criminal justice system. Although, there are several challenges (such as; the discretion of the judges, lack of facilities for the successful enforcement of non-custodial sentences, and corrupt practices) mitigating against its smooth implementation. It was therefore concluded and recommended that embracing non-custodial sentencing will reduce prison reception and minimize the enormous government resources in maintaining the prison infrastructure and the prisoners. In this regard, there is a need for a redress of the challenges mitigating the smooth application of non-custodian sentences in Nigeria's criminal Justice System.